PanamaTipico.com: a Born Digital Initiative for Researching and Preserving Panama’s Cultural Heritage - Marino Jaén Espinosa (Digital Presentation and Preservation of Cultural and Scientific Heritage, 2014)
This paper reflects on the experience of PanamaTipico.com, an independent website specialized in the research and preservation of the cultural heritage of the Republic of Panama, a developing country located in Central America. Basic information about the project is described. Also discussed, are some of the challenges confronted by the project and the results achieved. The goal of this paper is to encourage a discussion on whether or not the experience of PanamaTipico.com is comparable to the experiences of similar projects in developing countries in Eastern Europe and elsewhere.